Uji Formulasi Bacillus sp. Sebagai Pemacu Pertumbuhan Tanaman Padi Sawah (Oryza sativa L.) - Rinda Tinendung Tinendung; Fifi Puspita; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study aimed to examine the effect of formulations Bacillus sp. and to get the best formulations on the growth of rice (Oryza sativa L.). The research was conducted in Quarantine Laboratory in Pekanbaru and at Greenhouse, technical implementation unit of agriculture faculty of Riau University, in March until to August 2013. The methods of research is experimentally with using completely randomized design (CRD) with 5 treatments and 4 replications. The data were analyzed using analysis of variance and followed by Duncan's New Multiple Range Test at level 5%. The parameters measured were plant height, number of total tillers, number of productive tillers, panicle length, weight of 100 grains, percentage of grain pithy, weight of dry grain of each plant and dry weight of plant. The results of the research showing that the treatment of formulations Bacillus sp. has non significant effect on the growth of plant height, number of total tillers, number of productive tillers, panicle length, weight of 100 grains, percentage of grain pithy, dry weight of grain of each plant and dry weight of plant. Formulations of Bacillus sp. with waste oil palm is the best formulation because it can stimulate the growth of panicle length, increasing the weight of 100 grains, percentage of grain pithy, dry weight of grain in each plant and dry weight of plant. Keywords : Bacillus sp, formulation and paddy.